Penilaian Risiko Kesehatan Berbasis Keamanan Pangan Akibat Paparan Logam Berat dalam Biji Kedelai pada Sistem Pertanian Berkelanjutan - Sapto Priyadi Priyadi; Wiyono; Haryuni (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
Heavy metals rank high among the hazardous contaminants in the fresh produce of plant origin, originating from growing media and contaminated air environments. Plants absorb heavy metals depending on the availability of heavy metal ions in the soil and anthropogenic activities using agrochemicals. The entry of heavy metals into the human body through the tropic level can cause various chronic diseases; so regular monitoring of the presence of heavy metal contaminants in fresh products of plant origin is critical. Testing for heavy metal contaminants in plant tissues using an atomic absorption spectrophotometer – flame. The research results showed that the heavy metal contaminant Cd was not detected in the pre-cultivated agricultural land. In plant tissues, Pb in the pre-cultivated land was detected at 49,271 ± 0,423 mg kg–1, while Cu in the pre-cultivated land was 87,369 ± 0,867 mg kg–1, and in soybean seed tissue 12,571 ± 0,698 mg kg–1. Based on research results for Cu contaminants, show that a THQ value of 0.001 means that it does not have the potential to suffer chronic non-carcinogenic health consequences. This situation is reinforced by the THQ < RfD value means that stakeholders to be vigilant about reducing Cu contaminants on agricultural land, by consistently implementing good agricultural practices.